Drug Resistance and Substance Use Among Male and Female Adolescents in Alternative Secondary Schools in Guanajuato, Mexico - Kulis, Stephen (Rutgers University, 2012)
OBJECTIVE: Research is limited on the strategies that Mexican adolescents use to resist use of alcohol, cigarettes, and other drugs. Cultural norms and gender socialization patterns concerning the acceptability of use of various substances by women and men influence Mexican youths in their responses to offers of substances. This study explored the drug-resistance strategies used by youth in the central Mexican state of Guanajuato, how their use predicted patterns of substance use, and how these associations differed by gender. METHOD: The analysis used cross-sectional survey data from 702 (60% male) students enrolled in eight alternative secondary education school sites in 2007. Participants reported the drug-resistance behaviors they used to deal with offers of alcohol, cigarettes, and marijuana. Past-12-month use of the four drug-resistance strategies employed most often by U.S. youth—refuse, explain, avoid, and leave (R.E.A.L.)—and any other strategies were measured. Composite measures of lifetime and recent use of alcohol, cigarettes, and marijuana were predicted in multivariate ordinary least squares regression analyses. Models were tested with and without controls for the frequency that respondents were offered substances and introduced gender interaction effects. RESULTS: Controlling for substance use offers, more frequent use of a wide repertoire of R.E.A.L. strategies predicted less consumption of alcohol and cigarettes, and using non-R.E.A.L. strategies predicted less marijuana consumption. All of these relationships were either stronger for males than for females or significant for males only. CONCLUSIONS: Gender differences exist in the impact of R.E.A.L. strategies on substance use among youth in Mexico. Despite a narrowing gender gap in substance use in Mexico, large exposure to and susceptibility of substance use remains. Developing effective prevention programs in Mexico based on teaching appropriate drug-resistance strategies and enhancing communication skills could aid in reducing substance use among Mexican adolescents.